SOLUBILITY OF COPPER IN SILICATE MELTS AS FUNCTION OF OXYGEN AND SULFUR FUGACITIES, TEMPERATURE, AND SILICATE COMPOSITION - Holzheid A.; Lodders K. (My University, 2001)
The solubility of Cu in silicate melts coexisting with liquid Cu(Fe) metal and liquid Cu(Fe) sulfide was determined experimentally at oxygen fugacities ranging from 10-9.1 to 10-13.6 bar and sulfur fugacities ranging from 10-2.5 to 10-6.3 bar at 1300°C. An iron oxide-free silicate of anorthite-diopside eutectic composition and a synthetic MgO-rich basaltic silicate (FeO-bearing) were used in the partitioning experiments. In S-containing systems, some of the metal reacted to metal sulfide. The silicates in the four systems investigated (Fe-free and S-free; Fe-containing and S-free; Fe-free and S-containing; Fe-containing and S-containing) had different colors depending on the dissolved Cu species and the presence of iron and/or sulfur.Irrespective of the presence of sulfur, the solubility of Cu in the silicate increases with increasing oxygen fugacity and metal/silicate partition coefficients for Cu decrease. Increasing the temperature from 1300°C to 1514°C increases the Cu solubility (decreases the metal/silicate partition coefficient) at an oxygen fugacity 0.5 log units below the iron-wustite (IW) equilibrium in the Fe-free, S-free and Fe-containing, S-free systems. We infer the presence of monovalent Cu+ (''CuO0.5'') in the silicate melt on the basis of the solubility of Cu as function of oxygen fugacity. Experiments containing iron yield a formal valence of ~0.5 for Cu at very low oxygen fugacities, which is not observed in Fe-free systems. The low formal valence is explained by redox reactions between iron and copper in the silicate melts.There is no evidence for sulfidic dissolution of Cu in the silicates but sulfur has indirect effects on Cu partitioning. Iron metal/silicate partition coefficients depend on oxygen fugacity and on sulfur fugacity. Sulfidic dissolution of iron and oxide-sulfide exchange reactions with Cu cause a small increase in Cu metal/silicate partition coefficients.We derive an activity coefficient (γCuO0.5) of 10 +/- 1 for liquid CuO0.5 at 1300°C for the silicate melts used here. A comparison with literature data shows that log γCuO0.5 increases in proportion to the mass percentages [CaO +(Al2O3)/2] in silicate melts.We recommend the following equations for Cu metal/silicate and sulfide/silicate partitioning for geochemical and cosmochemical modeling if silicate composition and the activity of Cu in the metal or sulfide is known: log Dmet/sil = -0.48 - 0.25 . log fO2 - log γCumetal + 0.02 . [CaO + (Al2O3)/2; wt%]silicate logDsul/sil=+0.76-0.25 . logfO2+0.25logfS2-logγCS0.5,sulfide+0.02 . [CaO+Al2O3/2;wt%]silicate. The derived Cu metal/silicate and metal/sulfide partition coefficients are applied to core formation in the Earth and Mars. The observed Cu abundances in the Earth cannot be easily explained by simple core-mantle equilibrium, but the observed Cu abundances for Mars are consistent with core-mantle equilibrium at low pressure and temperatures.